Condense the expression to the logarithm of a single quantity. (Assume all variables are positive.)

2logase3 (x) +2 log base3 (y) -2 log base 3 (z)

=. log base3 (x)^2 + log base3 (y)^2 -log base3 (z) ^2

= logbase3 (x)^2 (y)^2 - log base (z)^2

= log base 3 (x)^2 (y)^2 / (z) ^2

= log base 3 (xy/z) ^2

Secure Information

Content will be erased after question is completed.

Enter the email address associated with your account, and we will email you a link to reset your password.

Forgot your password?

Sign Up